1985
DOI: 10.1161/01.hyp.7.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine on stress-evoked hemodynamic and plasma catecholamine changes in spontaneously hypertensive rats.

Abstract: SUMMARY Cardiovascular hemodynamics (microspheres) and plasma norepinephrine and epinephrine levels at rest and during short-term shaker stress were investigated in conscious spontaneously hypertensive rats and Wistar-Kyoto rats, with or without oral taurine (1.5%) treatment for 8 weeks. Taurine effects were evaluated by comparing data on the taurine-treated and untreated rats. Taurine affected neither the resting hemodynamics nor the resting plasma catecholamine levels in spontaneously hypertensive and Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
2
20
0
Order By: Relevance
“…44,45 Taurine may also reduce blood pressure through attenuation of peripheral AngII activity, enhancement of the kinin-kallikrein system in the kidney, 46,47 or decreasing levels of epinephrine and norepinephrine. Additionally, as observed in the current study, taurine supplementation effectively normalizes high blood pressure in the most common animal models of hypertension, including: spontaneously hypertensive rats (SHR), 48 deoxycorticosterone acetate (DOCA)-salt rats, 49 and Dahl-S rats. 50 …”
Section: Discussionsupporting
confidence: 65%
“…44,45 Taurine may also reduce blood pressure through attenuation of peripheral AngII activity, enhancement of the kinin-kallikrein system in the kidney, 46,47 or decreasing levels of epinephrine and norepinephrine. Additionally, as observed in the current study, taurine supplementation effectively normalizes high blood pressure in the most common animal models of hypertension, including: spontaneously hypertensive rats (SHR), 48 deoxycorticosterone acetate (DOCA)-salt rats, 49 and Dahl-S rats. 50 …”
Section: Discussionsupporting
confidence: 65%
“…Tip-tapered PE-50 catheters (Clay Adams, Parsippany, NJ, USA) were introduced into the femoral artery and vein, respectively, and into the left ventricle through the right carotid artery. 22 - 30 All catheters were brought out through subcutaneous tunnels in the dorsal cervical region. The wounds were treated with 1% lidocaine and sutured.…”
Section: Methodsmentioning
confidence: 99%
“…2231 This shaker stress evoked responses that combined emotional arousal with consequent behavioral and, hence, skeletal muscle excitation. Since circulatory variables were most stable between 2 and 3 minutes, 22 the second hemodynamic measurement was made during this period, using a different set of radioactive microspheres, as already described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that differences in affective reactivity between individuals with and without a family history of hypertension are elicited only by fairly intense stressors (e.g., shock avoidance). It is tempting to point to evidence of high emotionality in spontaneously hypertensive rats 31 and suggest that genetic factors might contribute to a general hyperresponsiveness to environmental stimulation mediated by the limbic and hypothalamic areas that can be observed in physiological, behavioral, and affective parameters. In a series of studies, Baer and coworkers 3233 found that families with hypertensive fathers tend to exhibit more negative nonverbal behaviors (e.g., gaze aversion) than families without hypertensive parents, and that there may be some relation between the frequency of negative nonverbal behaviors in parents and the blood pressure levels of children.…”
Section: Discussionmentioning
confidence: 99%